Mitigating environmental toxicity with hydrogen nanobubbles: A mitochondrial function-based approach to ecological restoration - Han Bao; You Zhang; Shuang Lv; Shu Liu; Wenhong Fan (Environment International)
In biological systems, nanobubbles (NBs) effectively enhance hydrogen molecule retention and scavenging reactive oxygen species (ROS), but the underlying mechanisms remain elusive. To investigate this, we prepared hydrogen NB water samples with consistent dissolved hydrogen levels but varying NB densities to explore their physicochemical properties and effects on green algae (Chlorella vulgaris) under oxidative stress induced by copper ions (Cu2+) and cadmium ions (Cd2+). The results indicated a strong correlation between the hydrogen NB number density and the 25 % inhibitory concentration of Cu2+ over 24 h, with ROS removal efficiency increased with the NB number density. Gas chromatography showed that the hydrogen NBs in the solution had a high gas density that enhanced hydrogen transport into C. vulgaris. With regard to mitochondrial activity, hydrogen NBs were observed to enhance the function of mitochondrial complexes I and V and increase the mitochondrial membrane potential. Experiments with C. vulgaris mitochondrial electrodes showed that the electron transfer rates increased significantly in the presence of hydrogen NBs. We concluded that the high gas density of hydrogen NBs augments intracellular hydrogen delivery and strengthens mitochondrial functions.